(untitled) (Synthesis, 2026)
Background: This study examined whether the explosion of digital health trials in Africa masks persistent structural inequities in research investment. Methods: We conducted a cross-sectional audit of ClinicalTrials.gov through April 2026, comparing 23,873 African and 190,644 United States interventional trials and estimating temporal change with ARIMA models. Results: Africa contributed 238 relevant trials versus 8,113 in the United States, revealing a 34-fold absolute gap in research volume. Although African trial registrations increased 17.1-fold from 2000-2005 to 2021-2025, the gap with high-income regions persisted. In Uganda, institutions like National Drug Authority, Uganda National Council of Science and Technology, Infectious Disease Institute, Makerere University support research oversight and capacity, registry output is still low. This pattern reflects constrained trial leadership, dependence on externally funded protocols, and weak integration of digital health tools into routine health systems despite expanding mobile penetration (Kwizera et al., 2025; Nanvuma et al., 2025). These results indicate that methodological capacity gaps limit the quality and impact of African clinical research output (Amboka et al., 2024; Edem et al., 2021). Conclusion: Interpretation is limited by the use of a single registry and the absence of non-English trial databases, but is consistent with WHO and peer-reviewed evidence on global research inequities (WHO, 2025).